Examining motherhood on Instagram: Descriptive analyses of representations and narratives on the pregnant body in Social Media - Bogas Ríos, María José; Zarauza Castro, Jorge (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This research is an approach to the embodiment of maternity and motherhood concept through posts on Instagram. The main aim of this research is to analyze the representations of the pregnant woman's body through the visual creativity of content creators. This is a descriptive research that uses an analytical-synthetic method and a narratological approach. The research questions relate to the type of publication, its style, and the diversity of experiences shared by expectant mothers. 182 publications from three influencer profiles were analyzed during their pregnancy process. Key findings include that profiles defined by the Realmom movement share the most mathernal experiences.